Genome-wide characterization and expression of DELLA genes in Cucurbita moschata reveal their potential roles under development and abiotic stress - Luo, Weirong; Zhao, Zhenxiang; Chen, Hongzhi; Ao, Wenhong; Lu, Lin; Liu, Junjun; Li, Xinzheng; Sun, Yongdong (Frontiers in Plant Science, 2023)
DELLA gene family plays a key role in regulating plant development and responding to stress. Currently, many DELLA family members have been identified in plants, however, information on DELLA genes in pumpkin (Cucurbita moschata) is scarce. In this study, physical and chemical properties, gene structure and expression of CmoDELLA genes were examined in pumpkin. We found that seven CmoDELLA genes were identified in pumpkin, and they were unevenly classified into five chromosomes. CmoDELLA proteins were relatively unstable and their secondary structures were mainly made up α-helix and random coil. All seven CmoDELLA proteins contained typical DELLA domain and GRAS domain, however, motif numbers between CmoDELLA proteins were unevenly distributed, implying the complex evolution and functional diversification of CmoDELLA proteins. Cis-regulatory elements analysis revealed that CmoDELLA genes might play an essential role in regulating plant growth and development, and response to stress in pumpkin. Transcriptome data in the roots, stems, leaves and fruits demonstrated that CmoDELLA2, CmoDELLA3 and CmoDELLA7 were related to the stems development, CmoDELLA1, CmoDELLA4, CmoDELLA5 and CmoDELLA6 were associated with the fruits development. Furthermore, we found that CmoDELLA1 and CmoDELLA5 were up-regulated under NaCl stress. CmoDELLA1, CmoDELLA2, CmoDELLA3, CmoDELLA5, CmoDELLA6 and CmoDELLA7 were remarkably induced under waterlogging stress. While, all of the 7 CmoDELLA genes showed significantly induced expression under cold stress. The expression patterns under abiotic stress suggested that CmoDELLA genes might mediate the stress response of pumpkin to NaCl, waterlogging and cold, however, the functions of different CmoDELLA genes varied under different stress. Overall, our study provides valuable information for further research about the potential functions and regulatory networks of CmoDELLA genes in pumpkin.